2013
DOI: 10.1016/j.bpj.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Buffering in the Neurovascular Unit: Models and Sensitivity Analysis

Abstract: Astrocytes are critical regulators of neural and neurovascular network communication. Potassium transport is a central mechanism behind their many functions. Astrocytes encircle synapses with their distal processes, which express two potassium pumps (Na-K and NKCC) and an inward rectifying potassium channel (Kir), whereas the vessel-adjacent endfeet express Kir and BK potassium channels. We provide a detailed model of potassium flow throughout the neurovascular unit (synaptic region, astrocytes, and arteriole)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…Further support for the involvement of this K + -to-K IR mechanism is demonstrated by the ability of Ba 2+ to inhibit vasodilation evoked by neuronal stimulation in brain slice preparations (by 50-70%) [26,68]. Notably, the salient features of this mechanism have been successfully recapitulated by computer models [131,132]. These studies suggest that K IR channel activity in response to endfoot-derived K + is indeed a vitally important mechanism for NVC, although the possibility that K + could act indirectly through Ba 2+ -sensitive K IR channels in another cell type, such as neurons or astrocytes (Table 1), cannot currently be discounted.…”
Section: Vascular K Ir Channels As the External K + Sensors In Cbf Comentioning
confidence: 89%
“…Further support for the involvement of this K + -to-K IR mechanism is demonstrated by the ability of Ba 2+ to inhibit vasodilation evoked by neuronal stimulation in brain slice preparations (by 50-70%) [26,68]. Notably, the salient features of this mechanism have been successfully recapitulated by computer models [131,132]. These studies suggest that K IR channel activity in response to endfoot-derived K + is indeed a vitally important mechanism for NVC, although the possibility that K + could act indirectly through Ba 2+ -sensitive K IR channels in another cell type, such as neurons or astrocytes (Table 1), cannot currently be discounted.…”
Section: Vascular K Ir Channels As the External K + Sensors In Cbf Comentioning
confidence: 89%
“…In addition, it has been shown that downregulation of Kir4.1 channels affects overall ion gradients and also impairs glutamate uptake by astrocytes [12,13]. There are numerous theoretical analyses supporting the spatial relationship between passive and active modulation of [K + ] o by astrocytes and the initiation or maintenance of epileptiform activity [54][55][56]. Furthermore, cell depolarization and impaired ion gradients inhibit glutamate transporter function and cause transporter reversal, thus glutamate release from the cell, which could further affect neuronal excitability [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, they buffer potassium to regulate the excitability of the neurons (Newman et al, 1984, Simard and Nedergaard, 2004, Wallraff et al, 2006). This potassium buffering is also thought to contribute, at least in part, to the process of neurovascular coupling; i.e., the process of matching local cerebral blood flow to the local neuronal activity (Dunn and Nelson, 2010, Witthoft et al, 2013), however, the potassium buffering role in neurovascular coupling remains disputed (Metea et al, 2007). To perform the critical function of potassium buffering and osmotic homeostasis, astrocytes ensheath the cerebrovasculature with specialized processes called end-feet.…”
Section: Introductionmentioning
confidence: 99%